LOW-GRADE INFLAMMATION IN SUBCLINICAL HYPOTHYROIDISM: ROLE OF HIGHSENSITIVE C-REACTIVE PROTEIN - Kumar, Pradeep; Sharma, Preeti; Sharma, Rachna; Gupta, Gaurav; Chaudhary, Anchal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Subclinical hypothyroidism (SCH) patients may present with abnormal lipid profile more specifically in patients having thyroid-stimulating hormone (TSH) >10 mIU/L. Since the contradiction still lies with patients having TSH <10 mIU/L, so the role of high-sensitive C-reactive protein (Hs- CRP) may be important with the prediction of inflammatory cardiovascular risk. Methods: Recently diagnosed 30 SCH patients both male and female were recruited and compared 30 normal healthy adults. Age and body mass index (BMI) of the study population were noted. Thyroid profile including TSH, FT4, and T3 was measured by an enzyme-linked immunosorbent assay (ELISA). Total cholesterol, triglycerides, and high-density lipoprotein (HDL) cholesterol were measured by the CHOD-POD method, GPO-PAP method, and CHOD-POD/phosphotungstic method. Low-density lipoprotein (LDL) cholesterol and very low-density cholesterol were measured by Friedewald formula. Lipoprotein ratios were also calculated. An ELISA was also used for the estimation of Hs-CRP. Results: The significant results were obtained in this study. BMI was significantly (<0.01) elevated in patients' group compared to the control group. In the thyroid profile, TSH was significantly (<0.05) different between the groups. Total cholesterol, triglycerides, and LDL-cholesterol were significantly (<0.01) elevated in the case group. A significantly lower concentration of HDL cholesterol was observed in SCH patients when compared with control subjects. There was an elevated concentration of lipoprotein ratios in patients group. The mean concentration of Hs-CRP was highly significant between the groups. The level was higher in the case group compared to the control group. In patients' group, there was a positive association (β- 0.36) (confidence interval 95%–0.002–0.536) between TSH and Hs-CRP. This association was highly significant. Conclusion: SCH patients having TSH <10 μIU/ml were characterized by dyslipidemia and elevated Hs-CRP. Increased lipoprotein ratios and Hs-CRP may promote low-grade inflammation in SCH patients, by which cardiovascular risk can be developed.